Coexistence of Takayasu’s Arteritis in Patients with Inflammatory Bowel Diseases - Camilla de Almeida Martins; Ana Elisa Rabe Caon; Carolina Bortolozzo Graciolli Facanali; Carlos Walter Sobrado; Sergio Carlos Nahas; Rosa Maria Rodrigues Pereira; Reuma Margalit-Yehuda; Uri Kopylov; Natalia Sousa Freitas Queiroz (Gastroenterology Research and Practice)
Background. Takayasu’s arteritis (TA) and inflammatory bowel disease (IBD) are chronic inflammatory granulomatous disorders that have rarely been concomitantly reported in case reports and small case series. Objective. We report a series of seven cases of TA and IBD association in two referral centers with a comprehensive review of literature. Methods. We analyzed retrospectively the electronic medical charts of TA-IBD patients at the University Hospital of São Paulo, Brazil, and at the Sheba Medical Center at Tel Aviv University, Israel. Results. Overall, five patients had Crohn’s disease (DC) and two had ulcerative colitis (UC), and they were mostly female and non-Asian. All patients developed IBD first and, subsequently, TA. Two underwent colectomy and one ileocecectomy due to IBD activity, while three required cardiovascular surgery due to TA activity. Most patients are currently in clinical remission of both diseases with conventional drug treatment. Conclusion. Although the coexistence of TA and IBD is uncommon, both seem to be strongly associated through pathophysiological pathways.